Interfering peptides targeting protein–protein interactions: the next generation of drugs?. Issue 2 (February 2018) - Bruzzoni-Giovanelli, Heriberto; Alezra, Valerie; Wolff, Nicolas; Dong, Chang-Zhi; Tuffery, Pierre; Rebollo, Angelita
Highlights: Structure-based strategies allow more-specific targeting of protein–protein interactions (PPIs). Interfering peptides (IPs) become a promising alternative to small molecules to target PPIs. Some IPs have already arrived in clinical trials. Abstract : Protein–protein interactions (PPIs) are well recognized as promising therapeutic targets. Consequently, interfering peptides (IPs) – natural or synthetic peptides capable of interfering with PPIs – are receiving increasing attention. Given their physicochemical characteristics, IPs seem better suited than small molecules to interfere with the large surfaces implicated in PPIs. Progress on peptide administration, stability, biodelivery and safety are also encouraging the interest in peptide drug development. The concept of IPs has been validated for several PPIs, generating great expectations for their therapeutic potential. Here, we describe approaches and methods useful for IPs identification and in silico, physicochemical and biological-based strategies for their design and optimization. Selected promising in-vivo -validated examples are described and advantages, limitations and potential of IPs as therapeutic tools are discussed. Teaser: Today, by improving administration, stability and intracellular delivery, the interest in peptides as potential drugs is resurgent, especially for targeting the thousands of intracellular protein–protein interactions implicated in cellular homeostasis and pathological conditions